The Effect of Work Discipline and Career Development on the Work Productivity of Employees at the Education Office and the Culture of Wajo District - Harcang Harcang; Muhammad Guntur; Herman Herman; Risma Niswaty (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Human resources are seen as a very important organizational asset because humans are human resources who are always needed in every organizational activity . This research is a type of quantitative research that aims to determine and analyze how the influence of work discipline and career development on employee productivity at the Department of Education and Culture of Wajo Regency . The independent variable in this research is career development while the dependent variable is employee productivity . The population in this study were all employees of the Department of Education and Culture of Wajo Regency . Data were obtained using te k nik questionnaires, observation , documentation and interview . The data analysis method used is validity test, reliability test and correlation test. Te k nik data analysis used is descriptive analysis (percentage and mean), test asusmsi classic (normality test, linieratis, a test multicollinearity, heteroscedasticity test) regression test, t-test, test-f and test the delta coefficient of determination (R2 ). The results showed that work discipline and career development simultaneously affect the work productivity of employees at the Department of Education and Culture of Wajo Regency.